PENURUNAN TSS, BOD DAN COD LIMBAH CAIR INDUSTRI TAHU DI DESA CILONGOK KABUPATEN BANYUMAS MENGGUNAKAN SISTEM ZEOLIT TERAKTIVASI DAN TERIMPREGNASI TiO2 - Suyata Suyata; Irmanto Irmanto (Universitas Jenderal Soedirman, 2009)
Activated and impregnated TiO2 zeolite systems to reduce TSS, BOD, and COD of tofu industrial wastewater in Cilongok Villages had been developed. Activated and impregnated zeolite systems were expected to be able to reduce the concentration of TSS, BOD, and COD. Thus, the research was aimed to know the ability of zeolite systems to reduce the concentration of TSS, BOD, and COD of tofu industrial wastewater. The research used five difference loading rates of tofu industrial wastewater which were 160, 240, 320, 400, and 480 L m-2 day-1. The most effective loading rate was determined by analyzing the concentration of TSS, BOD, and COD before and after processing using zeolite systems. The reduced concentration of TSS, BOD, and COD was determined by filling the activated and impregnated zeolite with industrial wastewater for 24 hours continuously in 30 days. Sampling was done in every 5 days with loading rate of 320 L m-2 day-1. The results indicated that zeolite systems could reduce the concentration of TSS, BOD, and COD of tofu industrial wastewater. The optimum loading rate to reduce the concentration of TSS, BOD, and COD was 320 L m-2 day-1. The efficiency of acid activated zeolite system in reducing the concentration of TSS, BOD, and COD were 83.348%, 91.899%, and 90.700%, respectively. The efficiency of base activated zeolite system in reducing the concentration of TSS, BOD, and COD were 84.380%, 93.711%, and 91.928%, respectively. The efficiency of impregnated zeolite system in reducing the concentration of TSS, BOD, and COD were 82.410%, 90.711%, and 89.917%, respectively.